The Impact of Information and Communication Technology (ICT) on Educational Improvement - Jigarkumar G. Acharya (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2023)
Information and communication technology has become an inseparable part of human life and caused doing things more through the consumption of less time and cost. The present research aims to study the effect of information and communication technology on the educational improvement of third grade high school students in Khash-Iran. The research was a descriptive survey. The population included the third-grade high school students of Khash city who were about 1900 people studying in 35 educational units in 2010. The sample size was determined using Kirgizia and Morgan statistical tables and was determined to be 320 people. Random multistep method was employed for sampling among male and female students in proportion with the community size. A researcher-made 24-quenstion questionnaire with a grading scale of Likret type was used for data collection whose validity and reliability was confirmed by Cronbach’s α . The method of measurement type was used for data analysis; frequency distribution table, frequency percentage and diagram drafting were used descriptive statistics section, The Khi (chi-square), U Mann –Whitney and Kruskal-Wallis statistical tests were used in inferential statistics section with regard to the measurement scale. SPSS was used to analyze data. Research findings reveal that using information and communication technology is effective in increasing educational motivation, improving questioning skill, improving research spirit and raising school marks. It is generally effective on third grade high school students' educational improvement to a great extent. This effect was the same among male and female students with different average scores, ages and fields. However, its effect on vocational and high schools’ students was different.